Interleukin-10 production and T cell-suppressive capacity in B cell subsets from atherosclerotic apoE −/− mice - Rincón Arévalo, Héctor; Villa Pulgarín, Janny Alexander; Tabares, Jorge; Rojas, Mauricio; Vásquez, Gloria; Ramírez Pineda, José R.; Castaño, Diana; Yassin Noreña, Lina María (Springer Science and Business Media LLC, 2017)
The evidence regarding the role of regulatory B cells (Breg) in atherosclerosis are scarce, and there are contradictory data about their atheroprotective properties. Due to the demonstrated protective function of Breg in different inflammatory diseases mainly through interleukin-10 (IL-10) production, the knowledge of their participation in atherosclerosis immunopathology would be very valuable. To further study which B cell subsets participate in IL-10 production and their regulatory role, splenocytes from apolipoprotein-E-deficient mice were evaluated by ex vivo and in vitro cultures. Atherosclerotic mice had increased frequency of IL-10+ B cells, which presented high CD1d, CD19, and IgM, but variable CD5, CD21, and CD23 expression. IL-10+ B cells were not enriched in B cell subsets previously reported as Breg. Increased frequency of IL-10+ B cells with transitional 1-like (T1-like) and follicular (FO) and reduced CD5+ and marginal zone (MZ) phenotypes were observed ex vivo. Increased frequency of IL-10+ B cells with T1-like and MZ, and decreased IL-10+ FO and T2 phenotypes were also observed in vitro. To determine regulatory capacity of B cells in the atherosclerotic model, each subset were co-cultured with CD4+CD25- T cells. CD5+, FO, MZ, and T1-like cells from atherosclerotic mice exhibited regulation in an IL-10-dependent manner. However, only FO cells decreased both frequency of interferon gamma (IFN-γ)+ and tumor necrosis factor alpha (TNF-α)+ and proliferation of T cells. Finally, splenocytes showed increased frequency of IFN-γ+ and TNF-α+ cells only when FO-depleted B cells were evaluated. These results suggest that mainly FO B cells can modulate in some level the inflammatory responses observed in atherosclerosis.
Keywords: Apolipoprotein-E-Deficient Mice; Atherosclerosis; Follicular B Cells; Il-10; Regulatory B Cells; Células T